Analisis Faktor-Faktor Penyebab Keterlambatan Pelaksanaan Proyek Pembangunan Jalan Dan Jembatan Di Kabupaten Karo - Poppy Yosephine (Jurnal Teknik Sipil USU, 2021)
The problem of transportation and access to small areas is one of the factors that delays the development of a region. Therefore, it is necessary to pay attention to the construction of the facilities so that they are suitable for use. However, in the construction of transportation facilities such as roads and bridges to these small areas, sometimes there are obstacles and delays. Therefore, we will discuss what problems could be the cause of the delay in the construction of roads and bridges. The research is focused on Karo Regency, because Karo Regency is a developing area and experienced about 7 delays in the construction of roads and bridges within a period of 3 years. Therefore, it will be summarized what are the factors of delay in Karo Regency so that it can be provided in the future. This research is thorough by using questionnaires which are distributed by Random Sampling method to the related contractors, and the data is processed using the SPSS application or the Statistical Package for Social Sciences to classify the factors that are very influential on the less influential.Keywords: Construction Delay in Road and Bridge Construction, Random Sampling Method and SPSS